Respuesta :
The answer is D
2x - 3y = 6 multiply this by -3
3x - y = 2 Multiply this by 2
-6x + 9y = -18
6x - 2y = 4 Add the 2 equations:-
7y = -14 so y = -2
Substitute y = -2 in second equation:-
3x - (-2) = 2
3x = 2-2 = 0
x = 0
solution is (0,-2)
2x - 3y = 6 multiply this by -3
3x - y = 2 Multiply this by 2
-6x + 9y = -18
6x - 2y = 4 Add the 2 equations:-
7y = -14 so y = -2
Substitute y = -2 in second equation:-
3x - (-2) = 2
3x = 2-2 = 0
x = 0
solution is (0,-2)
Answer:
d
Step-by-step explanation:
The step multiply x by 2 in the first equation and subtract the second equation will NOT produce a system with the same solution. The entire equation must be multiplied by 2.
Given a system of two equations in two variables, replacing one equation by the sum of that equation and a multiple of the other produces a system with the same solutions.